Adenoid cystic carcinoma of the external auditory- A Case Report - Khabti Almuhanna; Abdullah Alfulaij (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Background: Primary external auditory canal (EAC) malignancies are very rare with adenoid cystic carcinoma (ACC) representing approximately 5% of these tumors. There is insufficient knowledge of the natural behavior of ACC in EAC. The disease needs early detection and complete treatment because of  its tendency to recur, vicinity to sensitive organs and lower response to radiation. Case presentation: In this case study, we presented a case of young female (37 years old) with right external auditory canal (EAC) mass which was diagnosed as benign tumor, postoperative biopsy confi rmed it as ACC of the EAC which is a rare case in the literature. Conclusion: Here, we report a rare case of Adenoid Cystic Carcinoma (ACC) of External Auditory Canal (EAC) in a 37 years old Saudi female. Initial, Clinical and CT findings were suggestive of a benign cystic mass but histopathology examination confirmed that tumor was ACC of EAC. The patient underwent to radical excision of the tumor along the parotidectomy. Postsurgical recovery was uneventful with no sign of recurrence until two years of follow up.